Patrimonio territoriale e coralità produttiva: nuove frontiere per i sistemi economici locali - Dematteis, Giuseppe; Magnaghi, Alberto (Scienze del Territorio, 2018)
The territorialist alternative to a development model menacing to destroy life contexts is based on experimenting and networking new forms of ‘bottom-up’ local development, based on the enhancement of territorial heritage as common good. These actions are unified by the practice of ‘commoning’, of ‘common doing’, which is to say the management and the deliberately uncompetitive care of local resources. Such practices testify a rediscovery of “place consciousness”, a widespread sharing of economic production aims that include a ‘socio-territorial responsibility’ oriented towards the wellbeing of dwellers and places. The paper analyses the roots of this kind of approach, presenting a wide reflection that goes from the historical forms of land ownership to the theories of local development affirmed since the second half of the last century. The paper illustrates the various kinds of local action tools used in the various practices under consideration, outlining the common characters emerging from their analysis.